Cystosarcoma phyllodes A malignant cystosarcoma phyllodes in a 14-year-old girl - Öğün, Dinçer; Günhan, Ömer; Göze, Fahrettin (The Turkish Journal of Pediatrics, 1986)
The case of a 14-year-old girl with a malignant cystosarcoma phyllodes is presented. The lesion had grown rapidly and metastasized to the axillary lymph nodes, lung, bone and liver.